Konsep dasar manajemen perpustakaan dalam mewujudkan mutu layanan prima dengan sistem temu kembali informasi berbasis digital - Andi Ibrahim (Program Studi Ilmu Perpustakaan UIN Alauddin, 2014)
The satisfaction of library users is an indication to know how successful a library in giving good services. It is involved in the way how communication is being conducted and librarian behave to guide, direct, and provide information to its users. From here, library can show its roles when facing information technology today. The development of information technology has given a chance for library to develop its online retrieval system in which it can be used to help user to find the needed information. It is therefore important to note by all libraries around the world to consider today environment that the technology has been involved in many kind of human activities, including in library routines. Due to a library is a service organization, the main aim is to give good services and satisfying library users. One effort is IRS, Information Retrieval System.